Application of Solvent Extraction for the Removal of Amoxicillin Drug Residues in Environmental Waters: Application of Solvent Extraction for the Removal of Amoxicillin Drug Residues in Environmental Waters - Seifollahi, Zahra; Abbasi, Ali; Rahbar-Kelishami, Ahmad (Iranian Journal of Pharmaceutical Sciences, 2019)
In this study, removal of amoxicillin ions from aqueous medium by liquid-liquid extraction (LLE) technique was investigated. The LLE process coupled by UV-Visible spectroscopy was carried out by response surface methodology (RSM) based on central composite design (CCD). The process parameters such as extractant concentration, feed acidity, extraction time and diluent type were optimized. At these condition the maximum AMOX extraction was found to be 93.5 % and 96 % using TEA and MDEHPA, respectively. The findings of this study shows that solvent extraction process under the optimum conditions show the considerable potential for environmentally friendly and amoxicillin removal from aqueous media.